Kawasaki Disease with Retropharyngeal Edema following a Blackfly Bite - Toru Watanabe (Case Reports in Pediatrics)
We describe a patient with Kawasaki disease (KD) and retropharyngeal edema following a blackfly bite. An 8-year-old boy was referred to our hospital because of a 3-day-history of fever and left neck swelling and redness after a blackfly bite. Computed tomography of the neck revealed left cervical lymph nodes swelling with edema, increased density of the adjacent subcutaneous tissue layer, and low density of the retropharyngeum. The patient was initially presumed to have cervical cellulitis, lymphadenitis, and retropharyngeal abscess. He was administered antibiotics intravenously, which did not improve his condition. The patient subsequently exhibited other signs of KD and was diagnosed with KD and retropharyngeal edema. Intravenous immunoglobulin therapy and oral flurbiprofen completely resolved the symptoms and signs. A blackfly bite sometimes incites a systemic reaction in humans due to a hypersensitive reaction to salivary secretions, which may have contributed to the development of KD in our patient.